Case Report: Metreleptin Treatment in a Patient With a Novel Mutation for Familial Partial Lipodystrophy Type 3, Presenting With Uncontrolled Diabetes and Insulin Resistance - Lambadiari, Vaia; Kountouri, Aikaterini; Maratou, Eirini; Liatis, Stavros; Dimitriadis, George D.; Karpe, Fredrik (Frontiers in Endocrinology, 2021)
Background: Familial partial lipodystrophy type 3 (FPLD3) is a very rare autosomal dominant genetic disorder which is caused by mutations in the peroxisome proliferator activated receptor gamma (PPARG) gene. It is characterized by a partial loss of adipose tissue leading to subnormal leptin secretion and metabolic complications. Metreleptin, a synthetic analogue of human leptin, is an effective treatment for generalized lipodystrophies, but the evidence for efficacy in patients with FPLD3 is scarce. Case presentation: We present a 61-year-old woman, initially misdiagnosed as type 1 diabetes since the age of 29, with severe insulin resistance, who gradually displayed a more generalized form of lipoatrophy and extreme hypertriglyceridemia, hypertension and multiple manifestations of cardiovascular disease. She was found to carry a novel mutation leading to PPARGGlu157Gly variant. After six months of metreleptin treatment HbA1c decreased from 10% to 7.9% and fasting plasma triglycerides were dramatically reduced from 2.919 mg/dl to 198 mg/dl. Conclusions: This case highlights the importance of early recognition of FPLD syndromes otherwise frequently observed as a difficult-to-classify and manages diabetes cases, in order to prevent cardiovascular complications. Metreleptin may be an effective treatment for FPLD3.